The Impact of Geopolitical Risk and Political Economic Uncertainty on Islamic Stock Returns in OIC Countries - Rahmadany, Zhahirah Adriana; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
ABSTRACT This research aims to determine the influence of geopolitical risk and political economic uncertainty on the return of Sharia stocks. The study focuses on countries belonging to the Organization of Islamic Cooperation (OIC). Panel data regression analysis technique is employed to test the hypotheses proposed in this research. Utilizing data sources such as the Geopolitical Risk Index (GPR), Economic Political Uncertainty Index (WUI), and Bloomberg terminal, the findings indicate that geopolitical risk and political economic uncertainty affect the return of Sharia stocks. Additionally, there are control variables such as exchange rates and inflation that also influence the return of Sharia stocks. All hypotheses in this study are accepted as the test results show that geopolitical risk and economic political uncertainty significantly positively impact the return of Sharia stocks in OIC countries. The limitation of this research lies in the sample, which only consists of OIC countries. This study contributes to the literature on the influence of geopolitical risk and political economic uncertainty on the return of Sharia stocks.